2011
DOI: 10.2332/allergolint.10-oa-0296
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Leukotriene Receptor Antagonists to Inhaled Corticosteroids Improved QOL of Patients with Bronchial Asthma Surveyed in Suburban Tokyo, Japan

Abstract: These results suggest that the frequency of visits to an emergency room was decreased by complementing the anti-inflammatory effect of ICS with further treatment of inflammation, particularly with LTRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…RCTs have confirmed the efficacy of leukotriene receptor antagonists (LTRAs) when added to ICSs in improving symptoms, lung function, quality of life, as well as asthma-related hospitalizations and mortality. 92 95 Yasui et al 96 showed that additional administration of oral pranlukast to ICSs in stable asthmatics provided additional clinical benefit. Interestingly, add-on oral pranlukast was found to significantly reduce the levels of alveolar nitric oxide, suggesting that the clinical benefit of oral pranlukast could be mediated by the reduction in peripheral airway inflammation.…”
Section: Long-acting β2 Agonistsmentioning
confidence: 99%
“…RCTs have confirmed the efficacy of leukotriene receptor antagonists (LTRAs) when added to ICSs in improving symptoms, lung function, quality of life, as well as asthma-related hospitalizations and mortality. 92 95 Yasui et al 96 showed that additional administration of oral pranlukast to ICSs in stable asthmatics provided additional clinical benefit. Interestingly, add-on oral pranlukast was found to significantly reduce the levels of alveolar nitric oxide, suggesting that the clinical benefit of oral pranlukast could be mediated by the reduction in peripheral airway inflammation.…”
Section: Long-acting β2 Agonistsmentioning
confidence: 99%
“…Randomized controlled trials have confirmed the efficacy of LTRAs when used as monotherapy or added to inhaled corticosteroids for improving asthma outcomes, including lung function, symptoms, asthma exacerbations, health-related quality of life, rates of hospitalization, and death due to asthma attacks 2124. In a recent study, Yasui et al25 showed that addition of oral pranlukast to an inhaled corticosteroid or an inhaled corticosteroid plus a long-acting beta-2 adrenergic agent in stable asthmatics provided additional clinical benefit.…”
Section: Contribution Of Leukotriene Modifiers To Asthma Treatmentmentioning
confidence: 99%
“…Unfortunately, not all GPs adhere to these guidelines [8]. In fact, evidence suggests under-treatment of asthmatics by Japanese physicians [9], and some studies have reported that GPs lag behind RS with regard to the management of asthma [8,10,11].…”
Section: Introductionmentioning
confidence: 99%